'I was forced here': perceptions of agency in second generation 'return' migration to Tonga. Issue 15 (7th December 2016) - Lee, Helen
ABSTRACT: Migrants' adolescent children sometimes live for periods of time in their parents' homeland; however, little attention has been paid to this in the literature on 'return' migration and transnationalism. This paper explores the experiences of overseas born Tongan youth spending time in high schools in Tonga, whether by choice or because they have been taken or sent due to concerns about their behaviour. The importance of these young people's perceptions of agency in relation to their move is considered as a factor in their responses to their experiences in Tonga. Other factors shaping those experiences include their family situation, the school they attend and the wider attitudes in Tongan society towards these young people. The paper also considers the question of agency in relation to the cultural expectations these overseas born youth must learn to meet, which entail significant restrictions on their behaviour yet are also a means of strengthening their cultural identity and sense of belonging.